Determinan Penggunaan Informasi Akuntansi Bagi Manajemen Usaha Mikro Kecil Menengah (UMKM) - Roby Aditiya (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The regression model used in this study is a multiple linear regression model with the help of SPSS. The sampling method for the study used the Random Sampling method (random) which obtained as many as 95 MSME owners/managers in Somba Opu District, Gowa Regency. The results showed that the variables of business scale, business age and accounting knowledge had a positive and significant effect on the use of accounting information in MSME’s Somba Opu District, Gowa Regency. The implication of this research is that MSME actors are expected to better understand and use accounting information, especially for financial information, to pay more attention because the existence of financial reports for MSMEs can help MSMEs in applying for credit to banks if they need capital. For the government and related agencies, they must help SMEs to use accounting information more, one of which is by holding trainings related to accounting information. In addition, further research with the same theme is expected to add other variables that can affect the use of accounting information, so that the results of the study can explain the contribution of all these variables to the use of accounting information.